A Family of Dinuclear Iron(II) SCO Compounds Based on a 1, 3, 4‐Thiadiazole Bridging Ligand. Issue 22 (5th August 2015) - Herold, Christian F.; Carrella, Luca M.; Rentschler, Eva
Abstract: Invited for the cover of this issue is the group of Eva Rentschler at the Gutenberg University, Mainz, Germany. The cover image shows a new dinuclear iron(II) SCO compound as a molecular switch illustrating temperature‐dependent spin state switching upon cooling or heating. The 1, 3, 4‐thiadiazole backbone of the bridging ligand was necessary to achieve the diamagnetic [LS–LS] ground state, so far not observed in related systems. Abstract : Such a spin transition is desirable, as these complexes might offer the longer‐term possibility of developing more dense information storage systems... Read more about the story behind the cover in the Cover Profile and about the research itself onp. 3632 ff .